VALIDITY AND RELIABILITY OF THE HUDL TECHNIQUE MOBILE APPLICATION COMPARED TO THE UNIVERSAL GONIOMETER TO ASSESS THE RANGE OF MOTION DURING NEURODYNAMIC TEST (Cuestiones de Fisioterapia, 2019)
Background: the measurement of the range of motion during neurodynamic tests is fundamental for assessment in physiotherapy. The need to use both hands to perform the tests makes quantification difficult in clinical practice. The development of mobile technology based on Smartphone applications allows measuring angular ranges. Objective: to analyze the validity of the Hudl Technique application, for the measurement of the range of motion of the knee extension during the Slump test and elbow extension in the standard median nerve neurodynamic test compared with the universal goniometer and to determine its intra- and inter examiner reliability. Material and method: 33 volunteers were included (66 cases) for the Slump test and 30 volunteers (60 cases) for the median nerve test. One evaluator quantified the range of knee and elbow extension in each of the tests with the mobile application and with the universal goniometer. Two other evaluators quantified the measurements with the application. Re-sults: the mobile application obtained an excellent level of agreement with respect to the goniometer (ICC = 0.90) for the Slump test and a good level of agreement for the median nerve test (ICC = 0.88). Inter- and intra-exami-ner reliability was excellent for both tests (ICC = 0.93-0.98). Conclusion: the measurement of knee joint extension and elbow extension range during the Slump neurodynamic tests and the standard median nerve using the Hudl Technique application has shown excellent to good agreement with the universal goniometer. And it has been shown to have excellent intra and inter-examiner reliability for the measurements of the neurodynamic tests of Slump and the standard median nerve.